Sociotechnical Coordination and Collaboration in Open Source Software - Bird, Christian (Proceedings of the 27th IEEE International Conference on Software Maintenance, 2011)
Over the past decade, a new style of software development, termed open source software (OSS) has emerged and has originated large, mature, stable, and widely used software projects. As software continues to grow in size and complexity, so do development teams. Consequently, coordination and communication within these teams play larger roles in productivity and software quality. My dissertation focuses on the relationships between developers in large open source projects and how software affects and is affected by these relationships. Fortunately, source code repository histories, mailing list archives, and bug databases from OSS projects contain latent data from which we can reconstruct a rich view of a project over time and analyze these sociotechnical relationships. We present methods of obtaining and analyzing this data as well as the results of empirical studies whose goal is to answer questions that can help stakeholders understand and make decisions about their own teams. We answer questions such as “Do large OSS project really have a disorganized bazaar-like structure?” “What is the relationship between social and development behavior in OSS?” “How does one progress from a project newcomer to a full-fledged, core developer?” and others in an attempt to understand how large, successful OSS projects work and also to contrast them with projects in commercial settings.